Evaluasi Tata Kelola dan Manajemen Risiko Unit Teknologi Informasi dan Pangkalan Data pada Perguruan Tinggi Keagamaan Islam Negeri XYZ dengan Menggunakan Framework COBIT 2019 - Sulistiyono, Agus; Kusrini, K (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The Information Technology and Data Base Unit (UTIPD) is one of the units at the XYZ State Islamic Religious College (PTKIN) which is tasked with managing and developing information system management, network and application maintenance, managing databases, and developing other information technology (IT). This research aims to evaluate governance and risk management at UTIPD at PTKIN XYZ. As a higher education institution that continues to develop, PTKIN XYZ relies heavily on information technology to support its operations, administration and academic activities. However, with the increasing complexity of information systems and associated risks, an in-depth evaluation of how IT governance and risk management is implemented is needed. The COBIT 2019 framework, which is an international standard framework for IT governance and management, is used in this research to assess IT governance and risk management capabilities at UTIPD. The primary focus of this evaluation is to determine the extent to which current IT governance practices meet expected standards, as well as to identify areas requiring improvement. This research includes an analysis of COBIT 2019 domains that are relevant to IT governance and risk management. The results of this research show that the APO07 domain and APO12 domain processes only obtained capability level 2 and obtained a gap value (GAP) of 1 each. In addition, this research also presents recommendations for improving IT governance and risk management at PTKIN XYZ, with the aim of Finally, to ensure that this university can utilize information technology optimally, reduce risks, and support the achievement of its strategic goals. It is hoped that the findings from this research can become a reference for PTKIN XYZ and other higher education institutions in strengthening IT governance and risk management.